Review of resilience assessment of coastal bridges to extreme wave-induced loads. (15th April 2019) - Qeshta, Ismail M.I.; Hashemi, M. Javad; Gravina, Rebecca; Setunge, Sujeeva
Highlights: A comprehensive review on resilience assessment of coastal bridges is presented. The discussion covers wave forces, bridge response, fragility and recovery models. The discussion outlines advances and challenges in resilience assessment research. Abstract: Coastal bridges are susceptible to severe damage due to wave-induced forces during extreme events such as coastal flooding, hurricanes, storm surges and tsunamis. As a direct impact of climate change, the frequency and intensity of these events are also expected to increase in the future. This paper presents a comprehensive review of a four-phase resilience assessment of coastal bridge structures, namely, (i) characterization of external wave-induced forces, (ii) structural response of bridges, (iii) vulnerability assessment of damaged components, and (iv) post-disaster recovery. The four comprehensive modules are adopted from the classic framework of PEER PBEE and constitute the integrated knowledge needed for the prediction of the resilience of infrastructure under extreme wave-induced loads. The study also presents new expressions for resilience restoration that simultaneously account for the time, resources (cost) and environmental impacts of different recovery options with variable importance levels to different stakeholders.